2014
DOI: 10.1038/srep05227
|View full text |Cite
|
Sign up to set email alerts
|

Common dysfunctional variants of ABCG2 have stronger impact on hyperuricemia progression than typical environmental risk factors

Abstract: Gout/hyperuricemia is a common multifactorial disease having typical environmental risks. Recently, common dysfunctional variants of ABCG2, a urate exporter gene also known as BCRP, are revealed to be a major cause of gout/hyperuricemia. Here, we compared the influence of ABCG2 dysfunction on serum uric acid (SUA) levels with other typical risk factors in a cohort of 5,005 Japanese participants. ABCG2 dysfunction was observed in 53.3% of the population investigated, and its population-attributable risk percent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
59
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 76 publications
(68 citation statements)
references
References 20 publications
4
59
1
1
Order By: Relevance
“…We and other groups [5][6][7][8][9] recently reported gout/ hyperuricaemia to have relatively strong genetic risk factors. More recently, and for the first time, we performed a GWAS with only clinically defined Japanese male gout cases in which 16 single nucleotide polymorphisms (SNPs) were replicated, and five gout-risk loci were identified including two novel loci (MYL2-CUX2 and CNIH-2).…”
Section: Introductionmentioning
confidence: 68%
“…We and other groups [5][6][7][8][9] recently reported gout/ hyperuricaemia to have relatively strong genetic risk factors. More recently, and for the first time, we performed a GWAS with only clinically defined Japanese male gout cases in which 16 single nucleotide polymorphisms (SNPs) were replicated, and five gout-risk loci were identified including two novel loci (MYL2-CUX2 and CNIH-2).…”
Section: Introductionmentioning
confidence: 68%
“…In a cohort of 5,005 Japanese participants, the ABCG2 genotype had a greater effect on SUA than did other epidemiological risk factors for hyperuricemia, such as body mass index and alcohol intake (142). This observation needs to be repeated in other populations; however, it suggests a broad utility for small-molecule therapies capable of correcting the expression defects in specific ABCG2 mutations (136).…”
Section: Abcg2 and Mrp4mentioning
confidence: 96%
“…ATP-binding cassette transporter, subfamily G, member 2 ( ABCG2/BCRP ) is a high-capacity urate transporter2 and expresses in both intestine3 and kidney4. We and others previously demonstrated that ABCG2 dysfunction by its common variants causes gout256 and hyperuricemia27 by decreasing urate excretion. However, the evaluation of intestinal urate excretion in humans is very difficult due to urate degradation by intestinal bacterial flora.…”
mentioning
confidence: 99%